(untitled) (Al-Mansour Journal, 2022)
The energy dissipation performance of lightweight reinforced concrete shear-walls. These shear walls are evaluated for their seismic efficiency when the structure is subjected to seismic stresses, and this efficiency is represented in terms of energy dissipation. -nonlinear time history analysis—was studied in the present research. Twelve models have been analyzed using a finite element approach by SAP 2000 software. These models were created for an eight-story structure that was subjected to a seismic load and an additional gravity load as dead and live. Different parameters were adopted, such as reinforcement ratio, compressive strength, and aspect ratio. The analysis results of the study indicate that there is an improvement in the energy dissipation of those walls, which depends on the approved parameters, as well as that there was no failure in any of the analyzed models.